Properties of Permeable Block According to Replacement ratio of Fly ash - Lee, Sang-Soo; Lee, Won-Gyu; Jo, Een-Seok (International Journal of Engineering and Technology, 2018)
Background/Objectives: The mass production of cement is a problem of environmental pollution, and the permeable block is made of cement, causing many problems such as efflorescence and CO2 generation.Methods/Statistical analysis: The existing permeable block is made of cement, resulting in efflorescence, resulting in clogged pores and shortening the replacement cycle, which is an economical problem. It is a chemical component of cement which is the main cause of efflorescence. It is considered that fly ash can be used as a cement replacement to prevent efflorescence and can be environmentally improved by recycling industrial by-products.Findings: As a result of the basic experiment, the fluidity, the air content, the flexural strength and the compressive strength of the paste were measured. As the fly ash replacement rate increases, the fluidity and air content tends to increase and the strength tends to decrease. The characteristics of the fly ash improve the workability, but the initial strength is reduced. In this experiment, the aggregate is added to the paste, and the density and the water absorption tend to decrease. Porosity and permeability coefficient increase until a certain replacement ratio, and then decrease. The strength tended to decrease in the same manner as in the basic experiment, and the optimum replacement ratio was within the range of 10-20 (%).Improvements/Applications: In order to increase the strength that is insufficient in this experiment, other mixing materials will be added in the next experiment.Â Â
Keywords: Permeable Block; Efflorescence; Fly ash; Coefficient of permeability; Industrial by-products